Analysis of the Urgency of Material and Main Aspects of the Essential Concept of Natural Science in Kurikulum Merdeka - Sapitri, Riska Dia; Susanti, Dian (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Understanding the urgency of the material and the main aspects of the essential concepts of science is very important in learning. This study aims to analyse the urgency of the material and the main aspects of the essential concept in learning Natural Sciences (IPA) in the Independent Curriculum at the junior high school level. The Independent Curriculum provides flexibility for educators in designing contextual learning that is relevant to the needs of students, so that the selection of essential materials becomes very crucial. This study uses quantitative descriptive analysis with a simple random sampling technique on science teachers in Mataram City. Data was collected through a Likert-scale questionnaire to measure the level of urgency of science materials and the essentiality of aspects of the learning process. The results showed that most of the science materials, such as